Potassium ion battery positive electrode material, preparation method thereof and potassium ion battery

By combining nano-scale polyanionic compounds and MXene materials in the positive electrode material of potassium ion battery, an efficient conductive network structure is formed, which solves the problems of poor conductivity and cycle stability of the positive electrode material of potassium ion battery, and significantly improves the rate performance and battery cycle life. , and reduces production costs.

CN119133441APending Publication Date: 2024-12-13SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411256728.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The current potassium ion battery positive electrode materials have poor conductivity and cycle stability, resulting in poor rate performance and short battery cycle life.

Method used

Using nano-scale polyanionic compounds and MXene materials loaded on polyanionic compounds, the conductivity and phase stability of the material are improved through specific mass ratios and preparation methods, forming a three-dimensional interconnected conductive network structure to inhibit the generation of side reactions.

Benefits of technology

It significantly improves the conductivity and cycle stability of the positive electrode material of potassium ion battery, extends the cycle life of the battery, and reduces production costs, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005034316890000101
    Figure BDA0005034316890000101
  • Figure BDA0005034316890000111
    Figure BDA0005034316890000111
  • Figure BDA0005034316890000121
    Figure BDA0005034316890000121
Patent Text Reader

Abstract

The invention relates to the field of potassium ion battery materials, and particularly provides a potassium ion battery positive electrode material, a preparation method thereof and a potassium ion battery, the potassium ion battery positive electrode material comprises a nanoscale polyanion compound and an MXene material loaded on the polyanion compound, the molecular formula of the polyanion compound is KVPO4F, according to the positive electrode material, the conductivity and the interphase stability of the material can be greatly improved through the nanoscale KVPO4F primary particles and the MXene material, the positive electrode material has a three-dimensional interconnected conductive network structure, abundant active sites are provided, the transfer of K < + > / electrons is remarkably accelerated, and the rate capability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of potassium ion battery materials, and in particular to a potassium ion battery positive electrode material and a preparation method thereof, and a potassium ion battery. Background Art

[0002] With the rapid development of renewable energy and electricity, the power grid is in urgent need of developing low-cost and convenient energy storage devices. As we all know, lithium-ion batteries, sodium-ion batteries, aluminum-ion batteries and potassium-ion batteries have been widely used, and each has its own characteristics in the energy market. Although lithium-ion batteries have been widely used in various fields due to their high energy density, the limited and uneven distribution of lithium resources in the earth's crust have hindered the application of lithium-ion batteries in power grids. Potassium-ion batteries have attracted much attention due to their low cost and abundant potassium resources. The redox electrode potential of potassium (K + / K: -2.93V) than the redox electrode potential of lithium (Li + / Li: -3.04V) is lower. + The radius ratio Li + and Na + It is much larger, so it is necessary to design a suitable electrode material to store potassium. The positive electrode materials used for potassium storage are mainly polyanion compounds, layered oxides, organic materials and Prussian blue analogues. Among them, polyanion compounds have excellent electrochemical capabilities due to their special structure. Among them, potassium vanadium fluorophosphate (KVPO4F), as one of the most important positive electrode materials for potassium ion batteries, has attracted much attention due to its high voltage output and energy density. KVPO4F is a polyanion compound with poor conductivity, resulting in poor rate performance. And because of its high operating voltage, it is prone to side reactions, which accelerates its capacity decay during the cycle. Summary of the invention

[0003] Therefore, the technical problem to be solved by the present invention is to overcome the defects of poor conductivity and cycle stability of the positive electrode material of potassium ion batteries in the prior art, thereby providing a positive electrode material and a preparation method thereof.

[0004] To this end, the present invention provides a potassium ion battery positive electrode material, comprising a nanoscale polyanion compound and a MXene material loaded on the polyanion compound, wherein the molecular formula of the polyanion compound is KMPO4F, wherein M is one or more of V, Fe, Mn, and Ni.

[0005] Furthermore, the MXene material is selected from one or more of vanadium carbide MXene materials, aluminum carbide MXene materials, and titanium carbide MXene materials; preferably, vanadium carbide MXene materials.

[0006] Furthermore, the mass ratio of the MXene material to the nanoscale polyanion compound is 1-4:2-6, preferably 1.5-2.5:3-4.

[0007] Furthermore, the particle size D50 of the nanoscale polyanion compound is 500-700 nm.

[0008] The present invention also provides a method for preparing a positive electrode material for a potassium ion battery, comprising the following steps: mixing a nano-scale polyanion compound and a MXene material in the presence of a solvent to obtain a mixed solution, and heating the mixed solution to obtain the positive electrode material for a potassium ion battery;

[0009] Optionally, the solvent is one or more of ethanol, methanol, water, and acetone;

[0010] Optionally, the mass volume ratio of the MXene material to the solvent is 1-4 g:50 mL;

[0011] Optionally, a surfactant is also added to the mixture;

[0012] Optionally, the heating treatment further includes washing and drying steps.

[0013] The surfactant may be poloxamer and / or polyethylene glycol.

[0014] Furthermore, the temperature of the heating treatment is 120-180° C., and the time is 6-15 h; preferably, the temperature of the heating treatment is 140-160° C., and the time is 8-12 h.

[0015] Furthermore, the preparation method of the nanoscale polyanion compound comprises the following steps:

[0016] The M source, potassium source, phosphorus source and fluorine source are mixed, ground and calcined to obtain a nano-scale polyanion compound;

[0017] Optionally, the M source comprises one or more of vanadium pentoxide, vanadium nitrate, vanadium halide, vanadium sulfate, vanadium phosphate, iron oxide, ferrous oxide, iron nitrate, iron halide, iron sulfate, iron phosphate, manganese oxide, manganese nitrate, manganese halide, manganese sulfate, manganese phosphate, nickel oxide, nickel nitrate, nickel halide, nickel sulfate, and nickel phosphate;

[0018] Optionally, the potassium source comprises one or more of potassium carbonate, potassium oxide, potassium nitrate, potassium halide, potassium sulfate, and potassium citrate;

[0019] Optionally, the phosphorus source comprises one or more of phosphoric acid, ammonium phosphate, and vanadium phosphate;

[0020] Optionally, the fluorine source comprises one or more of ammonium fluoride and sodium fluoride;

[0021] Optionally, the calcination temperature is 500-600°C and the calcination time is 1.5-3h.

[0022] The molar ratio of vanadium, potassium, phosphorus and fluorine elements in the vanadium source, potassium source, phosphorus source and fluorine source is 1:1:1:1.

[0023] Furthermore, the preparation method of the MXene material comprises the following steps:

[0024] The MAX phase is chemically etched under the action of an etchant to obtain a MXene material; preferably, the MAX phase is selected from V2AlC, V2GeC, Ti4AlN3, Ti3AlC2 or Ti2AlC; more preferably, the MAX phase is V2AlC.

[0025] Further, the etchant includes an acid solution and a fluoride; optionally, the fluoride includes one or more of sodium fluoride and potassium fluoride;

[0026] Optionally, the acid is one or more of hydrochloric acid solution, sulfuric acid solution, and nitric acid solution;

[0027] Optionally, the ratio of the mass of the MAX phase to the mass of the fluoride and the volume of the acid solution is 0.8-1.5 g: 0.8-1.5 g: 10-30 mL;

[0028] Optionally, the chemical etching time is 60-80h and the temperature is 80-100°C;

[0029] Optionally, the chemical etching further includes washing and drying steps.

[0030] In the present invention, ethanol and / or water are used for washing. Vacuum drying can be used for drying. The drying temperature can be 50-70° C. and the drying time can be 4-10 hours.

[0031] The present invention also provides a positive electrode plate, which comprises the positive electrode material for a potassium ion battery or the positive electrode material for a potassium ion battery prepared by the preparation method.

[0032] The present invention also provides a potassium ion battery, comprising the above-mentioned positive electrode plate.

[0033] The technical solution of the present invention has the following advantages:

[0034] 1. The potassium ion battery positive electrode material provided by the present invention comprises a nano-scale polyanion compound and a MXene material loaded on the polyanion compound, wherein the molecular formula of the polyanion compound is KVPO4F, and the positive electrode material can greatly improve the conductivity and interphase stability of the material through the nano-scale KVPO4F primary particles and the MXene material, and the positive electrode material not only has a three-dimensional interconnected conductive network structure, but also provides abundant active sites, which significantly accelerates the K + / Electron transfer improves the rate performance, improves the electronic conductivity of KVPO4F, reduces the resistivity of the electrode, and inhibits the agglomeration of particles to form a stable interface, thereby improving the cycle stability of the battery. The accordion-shaped MXene material loaded on KVPO4F effectively inhibits the occurrence of side reactions, which can increase the cycle life of the battery.

[0035] 2. The potassium ion battery positive electrode material provided by the present invention, in certain preferred embodiments, is selected from vanadium carbide MXene material (V2CT X ), in KVPO4F and V2CT X VFC bonds are formed on the interface, which effectively reduces the loss of F, improves the material stability, and thus has a longer cycle life and better rate performance.

[0036] 3. The potassium ion battery positive electrode material provided by the present invention, in certain preferred embodiments, controls the mass ratio of the MXene material to the nanoscale polyanion compound to be 1-4:2-6, especially 1.5-2.5:3-4, so that the material stability is better, and thus the cycle life is longer and the rate performance is better.

[0037] 4. The preparation method of the positive electrode material of a potassium ion battery provided by the present invention is simple in preparation, easy to operate, environmentally friendly, has a short preparation cycle, can greatly reduce production costs, and is suitable for industrial production. In some preferred embodiments, the heating treatment temperature is controlled to be 120-180°C and the time is 6-15h; in particular, the heating treatment temperature is controlled to be 140-160°C and the time is 8-12h, so that the material stability is better, and thus the cycle life is longer and the rate performance is better.

[0038] 5. The preparation method of the positive electrode material of the potassium ion battery provided by the present invention selects V2AlC as the MAX phase, so that the material stability is better, and thus the cycle life is longer and the rate performance is better. DETAILED DESCRIPTION

[0039] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0040] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0041] Example 1

[0042] The present embodiment provides a potassium ion battery positive electrode material, comprising a nanoscale polyanion compound and a MXene material loaded on the polyanion compound, wherein the molecular formula of the polyanion compound is KVPO4F. The mass ratio of the MXene material to the nanoscale polyanion compound is 2:3.5. The MXene material of the present embodiment is a vanadium carbide MXene material.

[0043] The preparation method is as follows: (1) Preparation of polyanionic compounds: 1 mol of V2O5, 1 mol of K2CO3, 2 mol of H3PO4 and 2 mol of NH4F are placed in an agate ball mill, and then 13 g of agate ball mill beads are added for ball milling. The ball milling speed is 600 r / min and the ball milling time is 9 h. After ball milling, the material is placed in a tubular furnace for calcination, and the temperature is increased to 550°C at a heating rate of 10°C / min, and calcined at 550°C for 2 h to obtain KVPO4F. The particle size D50 of KVPO4F detected by laser diffraction is 780 nm.

[0044] (2) Preparation of MXene materials: 1.0 g of NaF was slowly added to a polytetrafluoroethylene liner containing 20 mL of 12 mol / L concentrated hydrochloric acid, and magnetically stirred at room temperature for 15 min to completely dissolve the NaF to obtain a NaF solution; 1.0 g of V2AlC was slowly added to the NaF solution, and continued to stir for 30 min to mix it evenly, placed in a hydrothermal reactor, moved into a forced air drying oven, and reacted at 90 ° C for 72 h; after natural cooling, it was diluted with deionized water and centrifuged at 3500 rpm for 5 min, the upper layer of liquid was poured off, and it was continued to be washed with deionized water and anhydrous ethanol several times until the pH was > 6; then it was vacuum dried at 60 ° C for 6 h to obtain a vanadium carbide MXene material, whose molecular formula is: V2CT X . (Tx represents functional groups such as -OH, -O- and -F).

[0045] (3) Preparation of positive electrode materials for potassium ion batteries: 2.0 g of vanadium carbide MXene material was dispersed in 50 mL of anhydrous ethanol; 3.5 g of KVPO4F and 0.05 g of poloxamer were added, and the mixture was stirred for 4 h to form a uniform suspension; the suspension was transferred to a reactor, sealed and kept warm at 150 °C for 10 h, and the mixture was cooled to room temperature; the obtained product was washed alternately with deionized water and anhydrous ethanol, each washing 5 times; the washed product was vacuum dried at 60 °C for 5 h to obtain the positive electrode material for potassium ion batteries.

[0046] Example 2

[0047] The present embodiment provides a potassium ion battery positive electrode material, comprising a nanoscale polyanion compound and a MXene material loaded on the polyanion compound, wherein the molecular formula of the polyanion compound is KVPO4F. The mass ratio of the MXene material to the nanoscale polyanion compound is 2.5:3. The MXene material of the present embodiment is a vanadium carbide MXene material.

[0048] The preparation method is as follows: (1) Preparation of polyanionic compounds: 1 mol of V2O5, 1 mol of potassium oxide, 2 mol of ammonium phosphate and 2 mol of NH4F are placed in an agate ball mill, and then 13 g of agate ball mill beads are added for ball milling. The ball milling speed is 600 r / min and the ball milling time is 9 hours. After ball milling, the material is placed in a tubular furnace for calcination, and the temperature is increased to 550°C at a heating rate of 10°C / min, and calcined at 550°C for 3 hours to obtain KVPO4F. The particle size D50 of KVPO4F detected by laser diffraction is 800 nm.

[0049] (2) Preparation of MXene materials: 1.0 g of NaF was slowly added to a polytetrafluoroethylene liner containing 20 mL of 12 mol / L concentrated hydrochloric acid, and magnetically stirred at room temperature for 15 min to completely dissolve the NaF to obtain a NaF solution; 1.0 g of V2AlC was slowly added to the NaF solution, and continued to stir for 30 min to mix it evenly, placed in a hydrothermal reactor, moved into a forced air drying oven, and reacted at 80 ° C for 60 h; after natural cooling, it was diluted with deionized water and centrifuged at 3500 rpm for 5 min, the upper layer of liquid was poured off, and it was continued to be washed with deionized water and anhydrous ethanol several times until the pH was > 6; then it was vacuum dried at 70 ° C for 5 h to obtain a vanadium carbide MXene material, whose molecular formula is: V2CT X . (Tx represents functional groups such as -OH, -O- and -F).

[0050] (3) Preparation of positive electrode materials for potassium ion batteries: 2.5 g of vanadium carbide MXene material was dispersed in 50 mL of anhydrous ethanol; 3 g of KVPO4F and 0.05 g of poloxamer were added, and the mixture was stirred for 4 h to form a uniform suspension; the suspension was transferred to a reactor, sealed and kept warm at 160 °C for 9 h, and the mixture was cooled to room temperature; the obtained product was washed alternately with deionized water and anhydrous ethanol, each washing 7 times; the washed product was vacuum dried at 50 °C for 8 h to obtain the positive electrode material for potassium ion batteries.

[0051] Example 3

[0052] This embodiment provides a positive electrode material for a potassium ion battery, which is basically the same as that of Embodiment 1, except that the mass ratio of the MXene material to the nanoscale polyanion compound is 1.1:4.4.

[0053] This embodiment provides a method for preparing a positive electrode material for a potassium ion battery, which is basically the same as that of Embodiment 1, except that the amount of vanadium carbide MXene material in step (3) is adjusted to 1.1 g, and the mass of KVPO4F is adjusted to 4.4 g.

[0054] Example 4

[0055] This embodiment provides a positive electrode material for a potassium ion battery, which is basically the same as that of Embodiment 1, except that the mass ratio of the MXene material to the nanoscale polyanion compound is 1:1.

[0056] This embodiment provides a method for preparing a positive electrode material for a potassium ion battery, which is basically the same as that of Embodiment 1, except that the amount of vanadium carbide MXene material in step (3) is adjusted to 2.75 g, and the mass of KVPO4F is adjusted to 2.75 g.

[0057] Example 5

[0058] This embodiment provides a positive electrode material for a potassium ion battery and a preparation method thereof, which is basically the same as that of Embodiment 1, except that in step (3), "after sealing, keep warm at 120° C. for 15 hours" replaces "after sealing, keep warm at 150° C. for 10 hours".

[0059] Example 6

[0060] This embodiment provides a positive electrode material for a potassium ion battery and a preparation method thereof, which is basically the same as that of Embodiment 1, except that in step (3), "after sealing, heat preservation at 180° C. for 6 hours" replaces "after sealing, heat preservation at 150° C. for 10 hours".

[0061] Example 7

[0062] This embodiment provides a potassium ion battery positive electrode material, which is basically the same as Example 1, except that the MXene material in this embodiment is a titanium carbide MXene material.

[0063] This embodiment provides a method for preparing a positive electrode material for a potassium ion battery, which is basically the same as that of Embodiment 1, except that in step (2), "Ti2AlC" of the same mass is used instead of "V2AlC".

[0064] Example 8

[0065] This embodiment provides a positive electrode material for a potassium ion battery, which is basically the same as that of Embodiment 1, except that the molecular formula of the polyanion compound is KMnPO4F.

[0066] This embodiment provides a method for preparing a positive electrode material for a potassium ion battery, which is basically the same as that of Embodiment 1, except that 2 mol of MnO2 is used instead of 1 mol of V2O5 in step (1).

[0067] Comparative Example 1

[0068] This comparative example provides a potassium ion battery positive electrode material, which is basically the same as Example 1, except that it does not contain MXene material.

[0069] This comparative example provides a method for preparing a positive electrode material for a potassium ion battery, which is basically the same as Example 1, except that steps (2) and (3) are omitted.

[0070] Comparative Example 2

[0071] This comparative example provides a positive electrode material for a potassium ion battery, which is basically the same as Example 1, except that the polyanion compound used in this example is micron-sized.

[0072] This comparative example provides a method for preparing a positive electrode material for a potassium ion battery, which is basically the same as Example 1, except that step (1) is different. Step (1) of this comparative example is: weigh vanadium phosphate (VPO4), sodium fluoride, and potassium citrate according to a molar ratio of phosphorus, fluorine, and potassium of 1:1:1.1, and mix them evenly with ethylene glycol and water in a volume ratio of 1:1.5, and the concentration of the obtained mixed solution is 20 mg / mL. Then, the mixed solution is placed in a reactor and kept at 200°C for 48 hours. After the reaction is completed, the product is washed alternately with deionized water and anhydrous ethanol, each for 5 times, and finally the obtained KVPO4F is dried at 70°C for 8 hours. After drying, the material is placed in a tubular furnace for calcination, and the temperature is increased to 550°C at a heating rate of 10°C / min, and calcined at 550°C for 2 hours to obtain KVPO4F. The particle size D50 of KVPO4F detected by laser diffraction method is 1.2μm.

[0073] Experimental Example 1 Preparation and Electrical Performance of Positive Electrode

[0074] The positive electrode material prepared in each embodiment and comparative example was coated to obtain a positive electrode sheet according to the following method: the positive electrode material, the conductive carbon black Super P and the binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was used as a solvent to prepare a slurry. The slurry was evenly coated on an aluminum foil current collector, dried, and then rolled and die-cut into a positive electrode sheet for a small soft-pack battery. The surface density of the positive electrode sheet was 20 mg / cm 2 The surface resistance of each group of positive electrode sheets was tested using an impedance meter and the results are shown in Table 1.

[0075] Table 1 Performance of positive electrode

[0076]

[0077]

[0078] It can be seen from the table that compared with the comparative example, the surface resistance of the potassium ion battery positive electrode material prepared in each embodiment of the present invention is significantly reduced, indicating that the conductive performance of the potassium ion battery positive electrode material of the present invention is significantly improved.

[0079] Experimental Example 2 Preparation and Electrical Performance of Cells

[0080] The positive electrode material prepared in each embodiment and comparative example was coated to obtain a positive electrode sheet according to the following method: the positive electrode material, the conductive carbon black Super P and the binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was used as a solvent to prepare a slurry. The slurry was evenly coated on an aluminum foil current collector, dried, and then rolled and die-cut into a positive electrode sheet for a small soft-pack battery. The surface density of the positive electrode sheet was 20 mg / cm 2 .

[0081] The hard carbon material, carbon black and PVDF were mixed evenly in a mass ratio of 8:1:1 and then coated on the surface of the copper foil. After drying, they were rolled and die-cut into negative electrode sheets. The surface density of the negative electrode sheet was 9 mg / cm 2 . Glass fiber was used as the separator, and 1 mol / L KPF6 / EC-DEC-DMC (volume ratio of 1:1:1) was used as the electrolyte. Finally, the negative electrode sheet-separator-positive electrode sheet-separator were stacked in order from top to bottom, and the electrode group was obtained after stacking. The two bare cells were placed in an aluminum-plastic film outer packaging shell, and the electrolyte was injected after drying. After vacuum packaging, welding, standing and formation, the test battery was obtained.

[0082] Aging internal resistance: measured using a resistance tester.

[0083] The test steps and conditions for room temperature charging and discharging DCR (DC internal resistance): Under 25°C conditions, use 0.33C to calibrate the capacity, charge to 50% SOC (SOC is the state of charge), let it stand for 30 minutes, discharge at 3C conditions for 10 seconds, test the discharge DCR (recorded as CC), then replenish the power, charge at 3C conditions for 10 seconds to test the charging DCR (recorded as DC).

[0084] The test steps and conditions for low-temperature charge and discharge DCR: At 25°C, after calibrating the capacity at 0.33C, adjust the temperature to -20°C, let it stand for 4 hours, discharge at 1C for 10s, test the discharge DCR (recorded as CC), then replenish the power, charge at 0.05C for 10s to test the charge DCR (recorded as DC).

[0085] The test steps and conditions for the first effect are as follows: At 25°C, fully charge the battery cell at 0.33C and record the charge capacity C0. Then discharge it at 1C with 100% DOD (DOD is the depth of charge and discharge) and record the discharge capacity C1. The first effect is the ratio of C1 to C0.

[0086] The test steps and conditions for 3C constant current charging ratio and 3C rate discharge capacity: At 25℃, fully charge the battery, calibrate the capacity at 0.33C, and then charge at 3C constant current and constant voltage. Calculate the 3C constant current charging ratio according to the following formula. 3C constant current ratio = (3C constant current and constant voltage charging capacity / 0.33C calibrated capacity) * 100%. At 25℃, fully charge the battery, calibrate the capacity at 0.33C, and discharge at 3C after fully charging at 0.33C constant current and constant voltage. Calculate the 3C rate discharge ratio according to the following formula; 3C rate discharge ratio = 3C discharge capacity / 0.33C calibrated capacity*100%.

[0087] Determination steps and conditions for the number of cycles of 3C / 1C room temperature cycle end: At 25°C, the lithium ion batteries prepared in the examples and comparative examples were charged at a 3C rate and discharged at a 1C rate, and full charge and discharge cycle tests were performed until the capacity of the lithium ion battery decayed to 80% of the initial capacity, which was considered as the end of life, and the number of cycles was recorded. Each experiment in each group was measured three times and the average value was taken.

[0088] Table 2 Performance parameters of battery cells

[0089]

[0090]

[0091] As can be seen from the table, compared with Comparative Examples 1-2, the potassium ion battery first effect, 3C constant current charging ratio, 3C rate discharge capacity and 3C / 1C room temperature cycle number obtained by the potassium ion battery positive electrode material prepared in each embodiment of the present invention are significantly improved, while the internal resistance, room temperature charge and discharge DCR and low temperature charge and discharge DCR after aging are significantly decreased, indicating that the potassium ion battery of the present invention not only has higher conductivity and rate performance, but also has significantly improved cycle performance; especially Examples 1 and 2.

[0092] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A positive electrode material for a potassium ion battery, characterized in that: It comprises a nano-scale polyanion compound and a MXene material loaded on the polyanion compound, wherein the molecular formula of the polyanion compound is KMPO4F, wherein M is one or more of V, Fe, Mn and Ni.

2. The potassium ion battery positive electrode material according to claim 1, characterized in that The MXene material is selected from one or more of vanadium carbide MXene materials, aluminum carbide MXene materials, and titanium carbide MXene materials; preferably, vanadium carbide MXene materials.

3. The potassium ion battery positive electrode material according to claim 1 or 2, characterized in that The mass ratio of the MXene material to the nanoscale polyanion compound is 1-4:2-6, preferably 1.5-2.5:3-4.

4. A potassium ion battery positive electrode material according to any one of claims 1 to 3, characterized in that: The particle size D50 of the nano-scale polyanion compound is 500-700nm.

5. A method for preparing a positive electrode material for a potassium ion battery according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: mixing a nano-scale polyanion compound and a MXene material in the presence of a solvent to obtain a mixed solution, and heating the mixed solution to obtain a positive electrode material for a potassium ion battery; Optionally, the solvent is one or more of ethanol, methanol, and acetone; Optionally, the mass volume ratio of the MXene material to the solvent is 1-4 g:50 mL; Optionally, a surfactant is also added to the mixture; Optionally, the heating treatment further includes washing and drying steps.

6. The preparation method according to claim 5, characterized in that: The temperature of the heating treatment is 120-180°C, and the time is 6-15h; preferably, the temperature of the heating treatment is 140-160°C, and the time is 8-12h.

7. The preparation method according to claim 5 or 6, characterized in that: The preparation method of the nano-scale polyanion compound comprises the following steps: The M source, potassium source, phosphorus source and fluorine source are mixed, ground and calcined to obtain a nano-scale polyanion compound; Optionally, the M source comprises one or more of vanadium pentoxide, vanadium nitrate, vanadium halide, vanadium sulfate, vanadium phosphate, iron oxide, ferrous oxide, iron nitrate, iron halide, iron sulfate, iron phosphate, manganese oxide, manganese nitrate, manganese halide, manganese sulfate, manganese phosphate, nickel oxide, nickel nitrate, nickel halide, nickel sulfate, and nickel phosphate; Optionally, the potassium source comprises one or more of potassium carbonate, potassium oxide, potassium nitrate, potassium halide, potassium sulfate, and potassium citrate; Optionally, the phosphorus source comprises one or more of phosphoric acid, ammonium phosphate, and vanadium phosphate; Optionally, the fluorine source comprises one or more of ammonium fluoride and sodium fluoride; Optionally, the calcination temperature is 500-600°C and the calcination time is 1.5-3h.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The preparation method of the MXene material comprises the following steps: The MAX phase is chemically etched under the action of an etchant to obtain a MXene material; preferably, the MAX phase is selected from V2AlC, V2GeC, Ti3AlC2 or Ti2AlC; more preferably, the MAX phase is V2AlC.

9. A positive electrode sheet, characterized in that: The invention comprises the potassium ion battery positive electrode material described in any one of claims 1 to 4 or the potassium ion battery positive electrode material prepared by the preparation method described in any one of claims 5 to 8.

10. A potassium ion battery, characterized in that: Including the positive electrode sheet as described in claim 9.